Discurso e patrimônio cultural : a memória do exército brasileiro na Segunda Guerra Mundial - Vasconcelos, Cyndiane Escarlete Dias (2018)
This dissertation is theoretically embedded in debates on discourses, power, cultural heritage, collective memory, and tourism; having as an empirical focus spaces of memory of Brazil's participation in World War II. The general objective is to analyze how this memory is (re) constructed through cultural heritage and tourism in contemporary Brazilian society. The specific objectives are: to understand the importance of studies on memory and cultural heritage; reflect on the role of tourism in the selection of memories and their relation to cultural heritage; reflect on the role of the Brazilian Army in contemporary society; to contextualize the social and historical aspects of World War II; to contribute to the debates on Tourism in Sociology; map the cultural heritage that works the memory of World War II in Brazil; and to understand the different discourses about the memory of World War II in Brazil that emerge in the National Monument to the Dead of the Second War and in the Museum of the National Veterans Association of FEB. The main theoretical references are Foucalt (2012), Foucalt (1999), Bardin (2010), Pollack (1989), Gomes (2014), Moesh (2000) Gastal; Moesch (2007), Aguiar (2007), Anderson (2008), Hobsbawm (2012), Castells (1999), Hall (2012), among others that point out that tourism and cultural heritage are selectors of memories, influenced by power. The methodology used was Discourse Analysis and Content Analysis, Bibliographic Research, Direct Observation and Interviews. With field research at the National Monument to the Dead of World War II, and at the Museum of the National Association of Veterans of the Brazilian Expeditionary Force, both located in Rio de Janeiro-RJ. The main results indicate that the (re) construction of this memory through the Monument, wants to include other subjects besides ex-combatants. However, it reinforces the myth of the soldier warrior and silences the meaning that war had for these subjects. In the Association, it was perceived that this (re) construction wants to include other subjects, and wants to highlight the suffering that the war provoked for these subjects. Still, it has been realized that tourism contributes to the flow of visitors in both locations, but sometimes the tourist is seen as a consumer, and this memory is seen as a marketable product.